2022
DOI: 10.1177/03331024221075073
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal sensory integration in migraine: A study of the effect of visual stimulation on somatosensory evoked cortical responses

Abstract: Background Merging of sensory information is a crucial process for adapting the behaviour to the environment in all species. It is not known if this multisensory integration might be dysfunctioning interictally in migraine without aura, where sensory stimuli of various modalities are processed abnormally when delivered separately. To investigate this question, we compared the effects of a concomitant visual stimulation on conventional low-frequency somatosensory evoked potentials and embedded high-frequency os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
4
8
0
Order By: Relevance
“…The fission phenomena of the SIFI depend on visual cortex excitability, along with other association cortices [38][39][40][41][42]. The present finding of reduced proneness to SIFI provides further support on the hypothesis that migraine could be seen as a disorder of multisensorial integration [43,44] that follows a pathological condition of hyperexcitability of the primary visual cortex [45]. This is in line with previous studies using neurophysiological and neurostimulation techniques.…”
Section: Discussionsupporting
confidence: 91%
“…The fission phenomena of the SIFI depend on visual cortex excitability, along with other association cortices [38][39][40][41][42]. The present finding of reduced proneness to SIFI provides further support on the hypothesis that migraine could be seen as a disorder of multisensorial integration [43,44] that follows a pathological condition of hyperexcitability of the primary visual cortex [45]. This is in line with previous studies using neurophysiological and neurostimulation techniques.…”
Section: Discussionsupporting
confidence: 91%
“…27 Furthermore, increased low-frequency somatosensory evoked potentials habituation and early high-frequency oscillations in migraine patients have been recorded after bimodal stimulation, indicating the abnormal excitability level of thalamo-somatosensory loops, which may relate to the malfunction in multisensory integration. 37 These findings supported our implications that the impaired thalamo-cortical synchronization may be a major contributor to multimodal sensory symptoms in migraine patients. The present results verified and expanded on thalamo-cortical dysrhythmia in migraine patients found by prior studies.…”
Section: Discussionsupporting
confidence: 80%
“…Migraine patients have been demonstrated to show habituation deficit of the late gamma band range, reflecting a functional disconnection of the thalamus to the cortical regions that led to decreased intracortical lateral inhibition 27 . Furthermore, increased low‐frequency somatosensory evoked potentials habituation and early high‐frequency oscillations in migraine patients have been recorded after bimodal stimulation, indicating the abnormal excitability level of thalamo–somatosensory loops, which may relate to the malfunction in multisensory integration 37 . These findings supported our implications that the impaired thalamo–cortical synchronization may be a major contributor to multimodal sensory symptoms in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the degree of brainstem and parietal excitation was maximal, while the degree of inhibition was minimal, 24 hours before the onset of the headache. Of note, a recent study investigating the effects of concomitant visual and somatosensory stimulation in migraineurs between attacks suggests that the abnormal processing in sensory information is not limited to single modalities, but actually involves multisensory integration (174).…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 99%